2021
DOI: 10.3390/radiation1030019
|View full text |Cite
|
Sign up to set email alerts
|

Proton Therapy and Gliomas: A Systematic Review

Abstract: Background: Gliomas are primary cerebral tumors. Radiation therapy plays a key role in their treatment but with a risk of toxicity associated with the dose to and volume of normal tissue that is irradiated. With its precision properties allowing for the increased sparing of healthy tissue, proton therapy could be an interesting option for this pathology. Methods: Two reviewers performed a systematic review of original papers published between 2010 and July 2021 following PRISMA guidelines. We analyzed disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Further, the use of CTV expansions in SRT protocols are being evaluated for safety and efficacy, with mixed results; however, if shown to be clinically beneficial, this approach could be considered in the future for canine glioma patients. [36][37][38] Despite the variability reported outcomes in previous and more recent studies, there is emerging evidence that radiation therapy is a viable treatment option for canine glioma, with more promising durability of tumour control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the use of CTV expansions in SRT protocols are being evaluated for safety and efficacy, with mixed results; however, if shown to be clinically beneficial, this approach could be considered in the future for canine glioma patients. [36][37][38] Despite the variability reported outcomes in previous and more recent studies, there is emerging evidence that radiation therapy is a viable treatment option for canine glioma, with more promising durability of tumour control.…”
Section: Discussionmentioning
confidence: 99%
“…This would be challenging to evaluate in prospective, randomized clinical trial for the reasons mentioned above for why clinicians and clients may be more inclined to treated their dog with SRT instead of a prolonged fractionated radiotherapy treatment course, but the results of such study would likely provide valuable information for the field. Further, the use of CTV expansions in SRT protocols are being evaluated for safety and efficacy, with mixed results; however, if shown to be clinically beneficial, this approach could be considered in the future for canine glioma patients 36–38 . Despite the variability reported outcomes in previous and more recent studies, there is emerging evidence that radiation therapy is a viable treatment option for canine glioma, with more promising durability of tumour control.…”
Section: Discussionmentioning
confidence: 99%
“…A potential margin for dose escalation with PBT in GBM is an area of future research (80)(81)(82)(83)(84)(85). In a National Cancer Data Base (NCDB) analysis, PBT was associated with improved outcomes in OS in adult patients either with low-grade or high-grade gliomas.…”
Section: Studies' Limitations and New Perspectivesmentioning
confidence: 99%
“…With the use of Magnetic Resonance Imaging (MRI) or X-Ray to detect a specific location, a stereotactic biopsy decreases the risk of affecting nearby areas of the brain (26). Some physicians, however, concluded that due to the risk of hemorrhage and other complications, biopsies are just as dangerous as surgical removal of a glioma (27).…”
Section: Challenges Of Treatmentmentioning
confidence: 99%